Development and validation of cultural competence assessment tool for healthcare professionals, India - Balachandran, Parvathy; Karuveettil, Vineetha; Janakiram, Chandrashekar (Frontiers in Public Health, 2022)
Culture influences an individual's perception of “health” and “sickness”. Therefore, cultural competence assessment of healthcare professionals is very important. Existing assessment scales have limited application in India due to the nation's rich cultural diversity and heterogeneous healthcare streams. This study was undertaken to develop and validate a cultural competence assessment tool for healthcare professionals in India. A cross-sectional study using convenience sampling was conducted following all standard steps among 290 healthcare professionals in India. Item reduction was followed by estimation of validity and reliability. Responses were recorded on a five-point Likert scale, ranging from strongly disagree to strongly agree. The resultant tool, named Cultural Competence Assessment Tool–India (CCT-I) showed an acceptable internal consistency (Cronbach's alpha =0.734). Inter-rater agreement was 81.43%. Face, content, and construct validity were demonstrated. There was no statistically significant difference in cultural competence between the healthcare streams based on years of clinical experience. There was statistically significant difference between streams of healthcare (p-value =0.009) and also between dentistry and Ayurveda groups (p-value = 0.003). This comprehensive tool can be used as the first step toward designing cultural competence training of healthcare manpower and the establishment of culturally sensitive healthcare organizations.